INTEGRASI UNIT USAHA SIMPAN PINJAM (USP) MILIK KOPERASI KE DALAM BANK KOPERASI (Analisis Potensi dan Penguatan Finansial Koperasi Menuju Kemandirian) - Hasan, Ishak (JURNAL KEBANGSAAN, 2012)
As a business entity, Cooperation still faces fundamental problems such as lacking of financial support institutions that fully owned by Cooperation. Nowadays, there are financial institutions dealing with Cooperation such as BUKOPIN. However, the financial institution is not fully owned by Cooperation. Although the Bank was initiated by Cooperation, the institution have been transferred to be a private Bank. Therefore, it is important to initiate a financial institution owned by Cooperation by integrating units of savings and loans into a Cooperation Bank. If it can be done, then the bargaining position of Cooperation in the financial field will be stronger, and pride of Cooperation can be maintained.